The influence of partial sleep restriction on repeated sprint ability and reaction time in university athletes - Wannell, B. R.; Brunner, F. M. J.; Lovibond, Z.; Bond, B. O. (Frontiers in Sports and Active Living, 2025)
Introduction: Few studies have assessed the influence of acute sleep restriction on repeated sprint ability and reaction time, which are important characteristics of many sports. Additionally, no within-measures study has compared the acute effect of interrupting sleep to an equivalent quantity of sleep lost by going to bed late. This study examined the influence of sleep restriction, achieved by going to sleep late, or by interrupting sleep, on repeated sprint ability and reaction time.